Parliaments and coalitions : the role of legislative institutions in multiparty governance - Martin, Lanny W.; Vanberg, Georg, 1971- (Oxford : Oxford University Press, 2011)
This text reveals that parliaments play a much more important role in policymaking in parliamentary systems than is usually acknowledged. Based on an analysis of roughly 1300 government bills across five democracies, it paints a detailed picture of the treatment of government legislation in contemporary parliaments.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Coalition governments; Legislative bodies